A contraception record card for use in general practice - Froggatt, Clive (1977)
This paper describes a contraceptive record card and flow sheet. The aim of the card is to produce better surveillance of contraceptive care by promoting the collection and array of important information for clinical decision-making. The purpose of this paper is to initiate the adoption of a standardized card for general use.